2004
DOI: 10.1007/s11136-004-8751-3
|View full text |Cite
|
Sign up to set email alerts
|

Cross-cultural development and validation of a patient self-administered questionnaire to assess quality of life in upper gastrointestinal disorders: The PAGI-QOL�

Abstract: The PAGI-QOL is a valid and reliable instrument assessing quality of life in patients with dyspepsia, GERD, or gastroparesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
108
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 121 publications
(110 citation statements)
references
References 16 publications
(17 reference statements)
2
108
0
Order By: Relevance
“…Disorders-Quality of Life (PAGI-QOL) 242 • Functional Digestive Disorders Quality of Life Questionnaire (FDDQL) 243 • Nepean Dyspepsia Index (NDI) 227 • Impact on day-to-day activity scale 224 • Glasgow Dyspepsia Severity Score 244 • Quality of Life in Reflux and Dyspepsia Questionnaire (QOLRAD) 245 • Gastrointestinal Quality of Life Index (GIQLI) 246 QOL, quality of life. …”
Section: Box 5 | Qol Instruments For Functional Dyspepsiamentioning
confidence: 99%
“…Disorders-Quality of Life (PAGI-QOL) 242 • Functional Digestive Disorders Quality of Life Questionnaire (FDDQL) 243 • Nepean Dyspepsia Index (NDI) 227 • Impact on day-to-day activity scale 224 • Glasgow Dyspepsia Severity Score 244 • Quality of Life in Reflux and Dyspepsia Questionnaire (QOLRAD) 245 • Gastrointestinal Quality of Life Index (GIQLI) 246 QOL, quality of life. …”
Section: Box 5 | Qol Instruments For Functional Dyspepsiamentioning
confidence: 99%
“…Comment: The evaluation of symptom severity, based on findings from a patient questionnaire, could predict therapeutic resistance [48] and QOL [49].…”
Section: Nsaids Lda and Fdmentioning
confidence: 99%
“…Previous studies have reported that QOL affected by eating attitude, sleeping disorders and clinical symptoms was associated with severity of diseases in FD patients. 13,34 Kaji et al 35 have also reported that QOL was particularly disturbed in the PCS for FD-NERD overlap syndrome and in the MCS for FD-IBS overlap syndrome. These studies and our own results suggest that the PCS, one component of SF-8 score influenced by clinical symptoms, sleep disorders and eating attitude might affect a patient's decision to seek healthcare at a tertiary clinic.…”
Section: Discussionmentioning
confidence: 99%